Figurative Language in The Greatest Showman Movie - Shafiyya, Nasywa Fairuz; Dewi, A.A. Sagung Shanti Sari; Nyoman Tri Ediwan, I (Peneliti.net, 2026)
The present undergraduate thesis entitled Figurative Language in The Greatest Showman Movie is focused on the analysis of the figurative language proposed by Knickerbocker and Reninger (1959) contained in the movie. In dealing with communication, whether in formal or informal settings, people express or use language that contains meanings beyond its real definition through metaphors, hyperbole and so forth. Figurative language is a figure of speech that implies more than the dictionary definition. Figurative language is also widely used by movie scriptwriters to convey deeper messages and enhance emotion. The study used a descriptive qualitative method to analyze the data with the movie called The Greatest Showman being the primary data. The data were collected using a note-taking technique and an informal method was used to present the analysis of the collected data by explaining descriptions of each data thoroughly. The result revealed the findings included all types of figurative language proposed by Knickerbocker and Reninger. There were 29 data found with varying amounts for each type. Metaphor is the most predominant type found in the movie.